Pengaruh Penerapan Khiyar dalam Jual Beli Online terhadap Keputusan Pembelian - Puji Winarko; Bhaswarendra Guntur; Subekan Subekan (Jurnal Dinamika Ekonomi Syariah, 2020)
The purpose of this study: To determine the level of confidence of FSEI IAI students Pangeran Diponegoro Nganjuk in online buying and selling. This is to determine the level of knowledge of FSEI students IAI Pangeran Diponegoro Nganjuk about khiyar. To find out the effect of the application of khiyar in online buying and selling on purchasing decisions. This research uses a descriptive quantitative approach. In collecting this data the authors collect data by means of interviews, observations, questionnaires. This study resulted in a 63% level of confidence in students of the Faculty of Sharia and Islamic Economics (FSEI) IAI Pangeran Diponegoro Nganjuk. In the table of interpretation guidelines, the percentage level of 63% of online trading is high. Meanwhile, the percentage level of 81% shows that the level of knowledge of the students of the Faculty of Sharia and Islamic Economics (FSEI) IAI Pangeran Diponegoro Nganjuk about khiyar is at a very high level. And the application of online buying and selling khiyar significantly affects the dependent variable (purchase decision) of the IAI Pangeran Diponegoro Nganjuk Islamic and Islamic Economics Faculty (FSEI) students so that the hypothesis in this study is accepted.